United States foreign aid freezes: A wake-up call for African countries to increase health financing - Joseph Magoola (Journal of Interventional Epidemiology and Public Health)
In January 2025, the United States of America (US) suspended all foreign aid, pending reviews to ensure alignment with American strategic interests. This decision significantly disrupted humanitarian assistance and healthcare services, particularly in low-and-middle-income countries that have been the biggest beneficiaries of US aid. The suspension has exacerbated funding gaps in critical sectors, including disease prevention, maternal health, and emergency response. As a result, African governments must urgently reassess their health financing strategies, and reduce dependency on external donors through increased domestic resource mobilization, innovative financing mechanisms, and strengthened public-private partnerships. These strategies are essential to safeguard African healthcare systems against future financial uncertainties and external policy shifts.